Stature estimation from body dimensions in Han population of Southern China - Lu-Yao Xu; Fan-Zhang Lei; Jie-Xuan Lin; Ling Song; Xin-Yu Li; Qi Wang (Wolters Kluwer Medknow Publications, 2020)
Stature estimation is widely used for individual identification in forensic field. Previous studies have proposed several regression equations derived from a single population for this purpose. However, this may not be suitable for other populations because of different hereditary and environmental conditions. In this study, stature estimation equations for southern China Han population have been provided. The study was conducted on a sample population of 121 men and women aged 18-25 years. A total of 19 parameters, including stature, head, torso, and parts of upper limbs and lower limbs, were measured according to standard anthropometric procedures. Herein, the anterior superior spine-malleolus medialis line showed the highest correlation coefficient (r = 0.817) and was the most reliable predictor (R2 = 0.667) in men, while the best predictor for women was total leg length (R2 = 0.746) with the highest correlation coefficient (r = 0.863). The regression analysis results via multiple predictors showed a high accuracy in stature estimation. Moreover, the analysis of multiple regression predictors showed that the dimensions of lower limbs were more reliable for stature estimation compared to head, torso, and upper limb measurements. This study provided equations of stature estimation for southern China Han population which can be useful in cases of dismembered body.